2014
DOI: 10.1128/jcm.03195-13
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Validation of the HPV-Risk Assay, a Novel Real-Time PCR Assay for Detection of High-Risk Human Papillomavirus DNA by Targeting the E7 Region

Abstract: Persistent infection with high-risk human papillomavirus (HPV) is the causative agent for cervical cancer (1, 2). Testing for HPV DNA provides better protection against cervical cancer and its precursors, i.e., high-grade cervical intraepithelial neoplasia (CIN), compared to cytology (3-7). For primary cervical cancer screening, it is crucial that the HPV assays that are used are clinically validated to ensure optimal distinction between HPV infections associated with CIN grade 2 or worse (CIN2ϩ) and clinicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
70
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 35 publications
1
70
0
2
Order By: Relevance
“…The aforementioned meta-analysis demonstrated that the sensitivity and specificity of HPV testing are similar on self-as on cliniciantaken samples when validated PCR tests are used but not when signal amplification-based HPV assays are applied (12). The conclusions of this meta-analysis remain unchanged after the addition of recently published studies (12,(14)(15)(16). The pooled relative sensitivity and specificity of 19 studies using HC2 (Qiagen) in self-versus clinician-collected samples were 0.86 (95% CI, 0.82-0.91) and 0.96 (95% CI, 0.93-0.98), respectively (see Fig.…”
mentioning
confidence: 82%
“…The aforementioned meta-analysis demonstrated that the sensitivity and specificity of HPV testing are similar on self-as on cliniciantaken samples when validated PCR tests are used but not when signal amplification-based HPV assays are applied (12). The conclusions of this meta-analysis remain unchanged after the addition of recently published studies (12,(14)(15)(16). The pooled relative sensitivity and specificity of 19 studies using HC2 (Qiagen) in self-versus clinician-collected samples were 0.86 (95% CI, 0.82-0.91) and 0.96 (95% CI, 0.93-0.98), respectively (see Fig.…”
mentioning
confidence: 82%
“…HrHPV was detected by GP5+/6+ PCR enzyme immunoassay [56] or HPV-Risk assay (Self-screen B.V.) [57]. This study followed the ethical guidelines of the Institutional Review Board of the VU University Medical Center and University Medical Center Groningen.…”
Section: Methodsmentioning
confidence: 99%
“…The assay uses 16 specific primers amplifying within E6 and E7 regions of the HPV genome and permits the detection of 13 high risk genotypes (16,18,31,33,35,39,45, 51, 52, 56, 58, 59 and 68) and two low-risk genotypes (6 and 11). The presence of DNA of these HPV subtypes were detected by multiplex PCR amplification using type specific primers [14,15].…”
Section: Dna Isolation and Hpv Genotypingmentioning
confidence: 99%